THE DEVELOPING OF WRITING SKILLS IN THE SPELLING SECTION BY PROVIDING BRAIN-BASED LEARNING (BBL) FOR STUDENTS WITH LEARNING DISABILITIES GRADE 2 - Pasoedsang, Kanlaya; Saihong, Prasong (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of this research to improve spelling skills in the spelling section. By providing brain-based learning (BBL) for students with learning disabilities. Grade 2, pass the 70 percent criteria and study the behavior of learning to write spelling in the spelling section. target audience are students with learning disabilities Grade 2, Suksa Songkroh Thawatburi School, first semester of the academic year 2022, consisted of 5 students. The research instruments were: Individualized Educational Management Plan (IEP), Individualized Lesson Plan (IIP), spelling skill practice in spelling section. Spelling skill test and learning behavior observation form the statistics used to analyze the data were percentage, mean and standard deviation. The results are as followed. 1. The development of writing skills in the spelling section. By providing brain-based learning (BBL) for students with learning disabilities. In Prathomsuksa 2, 5 students found that the students had scores of writing skills in the spelling section from 33-41 points from a full score of 50. They had skills in writing words in the spelling section Mae Kong and Mae Kon passed the criteria. 70 percent of 3 people, representing 60.00 percent, not passing the criteria, 2 people, representing 40.00 percent, for writing skills in the spelling section, Mae Km. There are 5 students of 70% passing the criteria, representing 100.00 percent. 2. The behavior of learning to write spelling in the spelling section. By providing brain-based learning (BBL) for students with learning disabilities. At the elementary school level 2, it was found that the learning behavior of writing skills in the spelling of Mae Kong section, 2 students, representing 40.00 percent, had excellent learning behaviors and 1 person, representing a good level. 10.00 and passing level of 2 students, representing 40.00 percent. As for learning behaviors of writing skills in the mother spelling section, it was found that 2 students had excellent learning behaviors, representing 40.00 percent and good levels. 3 students, representing 60.00 percent, and learning behaviors of writing skills in the mother spelling section, found that 5 students had excellent learning behaviors, representing 100.00 percent.